Social Aspects of Food and Nutrition: An Overview - Gowder, Sivakumar J T (Journal of Ecohumanism, 2024)
This article explores the multifaceted social aspects of food and nutrition, examining how cultural, economic, and social factors influence dietary habits and health outcomes. It discusses sociological perspectives, including structural functionalism, conflict theory, and symbolic interactionism, highlighting their relevance to food and nutrition. The article also addresses food as a social problem, focusing on issues such as food safety, biotechnology, and dietary disorders, and the role of public health policies in managing these concerns. Cultural influences on food and nutrition are analyzed with examples from various societies, illustrating how traditional foods, religious beliefs, and globalization shape dietary practices. Social influences on eating behavior, including family, peer, and societal norms, are explored, emphasizing their implications for nutritional interventions. The article delves into socio-economic inequalities in nutrition, discussing barriers to healthy eating faced by low-income populations and proposing strategies to address these disparities. Finally, the emerging field of nutritional epigenetics is examined, considering its social and biological implications for long-term health outcomes.